Unsteady squeezing flow of a viscous MHD fluid between parallel plates, a solution using the homotopy perturbation method - Siddiqui, Abdul M.; Irum, Sania; Ansari, Ali R. (Mathematical Modelling and Analysis, 2008)
The present paper analyses the unsteady 2‐dimensional flow of a viscous MHD fluid between two parallel infinite plates. The two infinite plates are considered to be approaching each other symmetrically, causing the squeezing flow. A similarity transformation is used to reduce the partial differential equations modeling the flow, to a single fourth‐order non‐linear differential equation containing the Reynolds number and the magnetic field strength as parameters. The velocity functions are obtained for a range of values of both parameters by using the homotopy perturbation method. The total resistance to the upper plate is presented. First Published Online: 14 Oct 2010